CCAB Centre for Contemporary Arts - Belgrade. (Beograd : Centrre for Contemporary Arts - Belgrade, 2000)
Staff, Department for Exhibitions and Cultural Exchange, Department for Education and Documentation (School for History and Theory of Images), Media and Publishing Department, Design and Multimedia Studio, Projects Depot
Engels
boek
Keywords: Andelkovic, Dejan; Ilic, Ivan; Krgovic, Dobrivoje; Naskovski, Zoran; Radovanovic, Jelica; Ristanovic, Aleksandra; Todosijević, Raša Dragoljub